Analisis Penggunaan KRI Kelas Diponegoro Guna Mendukung Perdamaian Dunia dalam Maritime Task Force Unifil - Budhi, Verry Ikhsan; Niko Oktoria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study examines the effectiveness of the Diponegoro-class corvettes in supporting the Maritime Task Force (MTF) UNIFIL mission during 2018–2025. The central problem lies in the declining operational effectiveness of Indonesian warships, indicated by the decreasing trend of monthly hailing despite relatively high sea-going hours. The objectives are to assess the trend of hailing performance, to test the correlation between sea-going percentage and hailing, and to evaluate the seaworthiness of the Martadinata-class frigates as potential replacements. The research employed a mixed-methods approach with an explanatory sequential design, combining quantitative analysis of operational data (sea-going percentage, helicopter flight hours, repair activities, hailing counts) and qualitative interviews with former Indonesian Maritime Task Unit Commanders and Indonesian Navy officials. Results reveal a consistent decline in hailing since 2021, a significant correlation between sea-going percentage and hailing, and ANOVA tests confirming significant performance differences among vessels in hailing, helicopter operations, and repair activities. Qualitative findings emphasize technical limitations, sensor effectiveness, and helicopter integration as critical factors reducing performance. The conclusion highlights the need for modernization of naval assets, optimization of ship–helicopter integration, and the strengthening of networked maritime surveillance to ensure Indonesia’s contributions to peacekeeping operations remain effective and sustainable. Keywords: Diponegoro-Class, Hailing, MTF Unifil, Naval Diplomacy, Peacekeeping Operations.